Perfil dos trabalhadores da atenção básica em saúde no município de São Paulo: região norte e central da cidade Profile of the primary health care workers in the municipality of São Paulo: north and central regions of the city - Regina Maria Giffoni Marsiglia (Universidade de São Paulo, 2011)
Pesquisa do Observatório de Recursos Humanos em Saúde de São Paulo em 2009, com 87 UBS na região norte e centro da cidade. OBJETIVO: levantar o perfil dos trabalhadores das UBS, organizadas sob: Programas de Saúde, Saúde da Família e Mistas. METODOLOGIA: sexo, idade, naturalidade, escolaridade, formação, função e tempo de trabalho na UBS de 4.968 trabalhadores, e entrevistas com amostra de 621 trabalhadores, através do Sistema de Entrevista Telefônica Assistida por Computador (ETAC). RESULTADOS: 80,7% dos entrevistados eram mulheres, mas só 56,4% entre os médicos; 50,5% entre 21 e 40 anos de idade e 49,1% entre 41 e 60 anos; 61,4% naturais do município ; apresentaram escolaridade superior ao exigido para as funções exercidas; no nível superior, 13,9 % eram médicos; no médio, 21,3% eram auxiliares de enfermagem e, no operacional, 20,7% eram ACS; 40,1% trabalhavam na UBS há mais de 5 anos, 12,9% há mais de 10 anos e 6,3% há mais de 20 anos; 64,7% trabalhavam só na UBS, 46,7% tiveram experiência na área hospitalar; 92,3% dos que trabalhavam nas UBS de Programas de Saúde eram funcionários públicos estatutários e 77% dos das UBS de Saúde da família contratados via CLT, pelas instituições parceiras da SMS-SP. CONCLUSÕES: predominância de trabalhadores do sexo feminino; processos de consolidação e de renovação do contingente de trabalhadores, maioria natural do município de São Paulo, escolaridade superior à exigida para a função; predominância de médicos, auxiliares de enfermagem e agentes comunitários de saúde; processo de terceirização nas relações de trabalho. Research conducted by São Paulo's Observatory of Human Resources in Health in 2009. It investigated 87 unidades básicas de saúde (UBS - primary care units) located in the north and central regions of the city of São Paulo. OBJECTIVE: to survey the profile of the UBS workers. The UBS were organized under different models: Health Programs, Family Health and mixed. METHODOLOGY: information about the universe of 4,968 workers was surveyed in the SMSSP (Municipal Health Department of São Paulo) and interviews were conducted with a sample of 621 workers through the ETAC System (Computer-Assisted Telephone Interview). RESULTS: 80.7% of the interviewees were women, but only 56.4% among the physicians; 50.5% were aged 21-40 years and 49.1% were aged 41-60 years; 61.4% were born in the city of São Paulo; a great deal of them presented a higher level of schooling than what was required to perform the functions; in the superior level, 13.9% were physicians; in the middle level, 21.3% were nursing assistants; and in the operational level, 20.7% were ACS (Community Health Agents); 40.1% had been working at the UBS for more than five years, 12.9% for more than 10 years and 6.3% for more than 20 years; 64.7% worked only at the UBS, 46.7% had had a previous experience in the hospital area; 92.3% of those who worked at the Health Programs UBS were statutory civil servants, and 77% of those of the Family Health UBS were hired through Brazil's Labor Laws, by the partner institutions of the SMSSP. CONCLUSIONS: predominance of female workers; process of consolidation and renewal of the quota of workers; the majority was born in the city of São Paulo and had a level of schooling that was higher than what was required for the function; predominance of doctors, nursing assistants and community health agents; outsourced contracts of employment.